BEDMAP3 - Ice thickness, bed and surface elevation for Antarctica - gridding products ... - Pritchard, Hamish; Fretwell, Peter; Fremand, Alice; Bodart, Julien; Kirkham, James; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert; Blankenship, Donald; Casassa, Gino; et al. (NERC EDS UK Polar Data Centre, 2024)
We present here Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of Antarctica south of 60degS. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap1 and Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. This has filled notable gaps in East Antarctica, including the South Pole and Pensacola basin, Dronning Maud Land, Recovery Glacier and Dome Fuji, Princess Elizabeth Land, plus the Antarctic Peninsula, West Antarctic coastlines, and the Transantarctic Mountains. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica's ice, ... : We created the Bedmap3 classification mask and grids of surface elevation, ice thickness, bed topography and uncertainty from a combination of new and existing interpolations of discontinuous survey datasets (airborne ice thickness, ship-borne bathymetry), existing gridded datasets from satellite-based mapping of rock outcrops, surface topography and ice shelf thickness, and a compilation of grounding zone coastal features extracted from satellite analysis. These outputs were created in the ArcGIS Pro software package. Specific details are provided in the associated paper (Prichard et al.) ...